Ekonomi Islam sebagai kekuatan Ketiga antara Kapitalisme dan Sosialisme - Setiyowati, Arin (Fakultas Agama Islam, 2016)
Islam views the economic problem is not from the standpoint of the capitalist who gives freedom and ownership rights to individuals and promote business in pereseorangan. Nor does it from the standpoint of a socialist, who wants to eliminate all the rights of individuals and make them like a slave economy controlled by the state. But Islam justifies ready selfish without letting it destroy society.Under the Islamic economic system, accumulation of wealth by a group of people avoided and steps performed automatically to move the flow of wealth to the community members who have not fared well. Steeped in the system we will get weakness capitalist economic system that developed according to the concept of free competition and ownership rights is growing as a result of overly tight supervision and dictatorial attitude of the workers class and the lack of recognition of property rights to the property. Islamic economic system is a system that is fair and thorough as well as efforts to ensure the wealth accumulated not only to one group alone, but spread throughout the community.The values of Islamic Economics (ethical values), the distribution concept in Islamic economics deserves to be a practical solution in the container community economy Indonesia. Through the instrument Zakai, inheritance, endowments, donation and Alms, as well as contract-contract muamalah laden with fairness to all parties and upholds the cooperation into capital in the development of the informal sector or commonly known as the peoples economy is independent so mempu prop up the economy Nation to be free of debt and the intervention of foreign investment. Or colony paradigm menpermainkan Indonesia towards the ideology of the nations economy.